The Influence of Flip Chart Media Use on Elementary School Students' Creativity and Critical Thinking - Didik Herwanto; I Wayan Wesa Atmaja; Hariyanto Hariyanto (Universitas Muhammadiyah Mataram, 2026)
The development of higher-order thinking skills (HOTS), particularly creativity and critical thinking, has become a central priority in contemporary science education. However, limited access to digital learning resources in many rural elementary schools necessitates the exploration of alternative instructional strategies that remain pedagogically effective. This study aims to examine the effects of non-digital flip-chart media on the creativity and critical thinking skills of sixth-grade students in science learning. The development of creativity and critical thinking skills as part of Higher Order Thinking Skills (HOTS) is an important demand in 21st-century Education. However, limited learning facilities in rural elementary schools still hinder the implementation of innovative technology-based learning. However previous studies predominantly examine digital media interventions or focus on a single higher-order thinking skill, leaving limited empirical evidence regarding the simultaneous development of creativity and critical thinking through non-digital visual media in rural elementary school contexts. This gap highlights the need for contextual and integrative research that explores simple, accessible instructional media to foster Higher Order Thinking Skills (HOTS).This study used a quantitative approach with a one-group pretest–posttest design. Data were collected using validated creativity and critical thinking essay tests consisting of 10 items each, assessed with analytical rubrics. Statistical analyses included normality testing, paired sample t-test, Normalized Gain (N-Gain), and Cohen’s d effect size to determine both statistical significance and practical impact. The subjects were 27 sixth-grade students from Elementary School, selected using a total sampling technique. The research instruments were validated through expert judgment and empirically tested using Cronbach’s alpha to ensure reliability. Data were analyzed using paired sample t-test, N-Gain, and effect size (Cohen's d). The results showed that the use of flip chart media significantly increased students' creativity and critical thinking skills (p < 0.05). The increase in creativity was in the high category (N-Gain = 0.76), while the increase in critical thinking skills was in the medium category (N-Gain = 0.67). The effect size was very large for both variables. These findings indicate that non-digital flip chart media is an effective, practical, and contextually appropriate alternative for developing HOTS in elementary school students, particularly in science learning within technology-limited environments. Theoretically, this study reinforces the role of structured visual media in supporting higher-order cognitive processes, while practically, it offers an accessible instructional strategy for teachers in rural schools to foster creativity and critical thinking without reliance on digital infrastructure.These findings indicate that non-digital flip chart media is an effective, practical, and contextually appropriate alternative for developing HOTS in elementary school students, especially in science learning in environments with limited technological facilities.